Burn Wound Healing Effect of a Sterilized Traditional Formulation of Boswellia carteri vs. Silver Sulfadiazine Cream 1% in Patients Presenting Second-degree Burn Wounds: A Randomized, Double-blind Clinical Trial - Parmis Badr; Suleiman Afsharypuor; Hamid Reza Tohidinik; Ali Akbar Mohammadi; Saeid Daneshamouz (Iranian Journal of Medical Sciences, 2023)
Background: Burn wounds rank among the most serious healthcare issues. Many studies reported the effectiveness of natural products in the wound-healing process. The present study compared the effects of a standardized herbal formulation derived from Boswellia carteri (B. carteri) and silver sulfadiazine (SSD) cream 1% on the healing of burn wounds.Methods: This randomized double-blind clinical trial was conducted at Shiraz Burn Hospital (Shiraz, Iran) between July 2012 to August 2013. A sterilized formulation comprising B. carteri 40% was prepared. 54 second-degree burn patients of both sexes with age ranges of 20 to 60 were invited to participate in this double-blind, randomized clinical trial. They were randomly divided into two groups and given either the Boswellia formulation or SSD cream. The healing index was determined based on the wound area assessment using the planimetry technique. The Kaplan-Meier survival analysis was used to assess the primary outcome, which was the amount of time until complete healing.Results: The trial was completed by 17 patients from the SSD group and 15 patients from the Boswellia group. During the study period, both groups showed a progressive healing trend. The mean (95% CI) healing time in the SSD group was 10.94 (9.03-12.85) days and 10.73 (9.23-12.23) days in the Boswellia group (P=0.71), indicating no significant difference. On the 17th day, the healing index of all patients in the Boswellia group reached 1.Conclusion: Boswellia topical formulation had a burn wound healing effect comparable to that of the standard SSD 1% treatment. Based on the findings of this study, the likelihood of contact dermatitis with Boswellia should be taken into consideration.